Assessment of diversity and use status of wild edible plants in Barshong and Kikhorthang in Tsirang - Phurpa Wangmo (CNR, Lobesa Phurpa Wangmo, 2022)
includes acknowledgement and abstract
Keywords: BSc Thesis